Wide Spectrum of Active Compounds in Sea Buckthorn (Hippophae rhamnoides) for Disease Prevention and Food Production - Agnieszka Jaśniewska; Anna Diowksz (MDPI AG, 2021)
Growing demand for value-added products and functional foods is encouraging manufacturers to consider new additives that can enrich their products and help combat lifestyle diseases. The healthy properties of sea buckthorn have been recognized for centuries. This plant has a high content of bioactive compounds, including antioxidants, phytosterols, essential fatty acids, and amino acids, as well as vitamins C, K, and E. It also has a low content of sugar and a wide spectrum of volatiles, which contribute to its unique aroma. Sea buckthorn shows antimicrobial and antiviral properties, and is a potential nutraceutical or cosmeceutical. It was proven to help treat cardiovascular disease, tumors, and diabetes, as well as gastrointestinal and skin problems. The numerous health benefits of sea buckthorn make it a good candidate for incorporation into novel food products.